Evaluate sharp turns: A Systematic Literature Review Study - Purnama.R, Moch Yoga; Lesmana N, Vindhy; Endi S, Nanda; Rijaludin, Arief; Handayani, Susanty (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The development of roads is one of the things that goes hand in hand with technological progress and encourages economic growth. Road development facilitates and accelerates the circulation of goods and services between regions as the backbone of the nation's economy. Road development has been felt by various parties in making it easier and smoother for various types of economic activities carried out between regions. Roads have several facilities such as bends, slopes, intersections, and others. For the safety and comfort of traffic flow, road users need to pay extra attention when passing bends, slopes, and intersections. Periodic maintenance of various road facilities is crucial so that this infrastructure continues to function optimally in supporting economic development. Traffic accidents often occur on roads, especially those leading to tourist areas or mountains, with steep or dangerous curves as vulnerable locations. To overcome this problem, studies are needed to identify problems such as lack of signage, non-ideal road surfaces, or curve designs that are potentially dangerous. This case study highlights the potential of roads that affect road use due to the geometry of curves that have the potential for accidents. The purpose of this steep bend case is to evaluate comprehensively the existing curve geometry conditions in the case study of steep bends in hilly or mountainous areas.a steep curve located in hilly or mountainous areas that potentially impact road user safety.